Faktor Predisposisi Masyarakat Tetap Tinggal Di Wilayah Resiko Tinggi Bencana Di Kabupaten Garut - Zahara Farhan; Tantri Puspita; Devi Ratnasari; Cyntia Rianasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Garut Regency is one of the areas that have the highest potential for disasters in West Java with the most frequent types of natural disasters, namely earthquakes, landslides, flash floods, and tsunamis. The impact of those disasters inflicts many casualties, infrastructure damage, loss of property, paralyzed life activities, and the emergence of various diseases. However, this does not affect the community to remain in high-risk areas due to several factors underlying the community to remain in the region such as; social factors, environmental factors, economic factors, and cultural factors. This study's aim was to find out the most dominant factors that motivate the community to remain in high-risk disaster areas in Garut Regency This study was used as a cross-sectional method with a sample of 120 families. The sampling technique was purposive sampling with logistic regression analysis. Spearman rank test results showed that social and economic factors were factors that have a community relationship still living in high-risk areas of disaster ( p values = 0.02 and 0.01, respectively), The logistic regression test results indicate that environmental factors were the most dominant factor for the community to remain living in a high-risk disaster area in Cibatu Sub-District, Garut Regency with a 2.265 Wald at a 95% significance level. Social factors were not proven to be the most dominant factors among the 4 other factors in the background of the community still living in high-risk areas of disaster in the District of Cibatu, Garut Regency.